Spare Ribs? Early Modern Female Monasticism in the East Slavic Lands - Charipova, Liudmila V. (History compass, 2014)
In contrast to the robust state of research on female Catholic monasticism in Central and Western Europe, Italy and the Iberian Peninsula, the history of Orthodox and Greek Catholic convents in the Balkans and Eastern Europe remains a largely uncharted field of study. Although historical archives in those parts of Europe offer rich pickings of first-class documentary material, the lack of up-to-date research methodologies in post-Socialist countries, the current stunted condition of pre-modern Slavic studies in Western Europe and occasional problems of archival access create obstacles against the development of this promising area of research. However, characteristic of a strong element of human interest, research on early modern women's monasticism of the Eastern Rite, has the potential to broaden the awareness of the place women held in European societies and cultures of the past and contribute to a more nuanced understanding of it at present.